2022
DOI: 10.3390/su14084467
|View full text |Cite
|
Sign up to set email alerts
|

How Innovative Characteristics Influence Consumers’ Intention to Purchase Electric Vehicle: A Moderating Role of Lifestyle

Abstract: Electric vehicles have been identified as a viable option for optimization of the energy structure to foster energy conservation and a reduction in emissions, as well as to promote the development of a sustainable economy. Recently, China announced that the financial subsidies for electric vehicles will be gradually withdrawn, and many incentive policies will be revised, indicating that the electric vehicle market has transformed from a policy-driven to a market-driven structure. Therefore, we study the elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…Out of total 330 respondents, 52.7% were males and remaining 47.3% were females. (Ajzen, 2011;Xie et al, 2022) The respondents in the age group of 18-24 years, 25-34 years and 35-55 years were 11.8%, 49.4% and 38.8%, respectively. 57% respondents were working professionals by profession, 26.7% were businessman, 12.7% were student and remaining 3.6% were homemaker and retired person.…”
Section: Discussionmentioning
confidence: 99%
“…Out of total 330 respondents, 52.7% were males and remaining 47.3% were females. (Ajzen, 2011;Xie et al, 2022) The respondents in the age group of 18-24 years, 25-34 years and 35-55 years were 11.8%, 49.4% and 38.8%, respectively. 57% respondents were working professionals by profession, 26.7% were businessman, 12.7% were student and remaining 3.6% were homemaker and retired person.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the improvement of technological innovation capacity may lead to the improvement of charging pile technology [20]. Secondly, according to the "market-driven innovation theory" [21], the upgrading of scientific and technological innovation level may promote the development and innovation of new energy vehicles.Therefore, hypothesis 5 is proposed. Hypothesis 5: Technological innovation capacity and its spillover effect can promote the impact of charging piles on the market performance evaluation of local new energy vehicle enterprises.…”
Section: Moderating Effect Of the Number Of Charging Piles On The Fin...mentioning
confidence: 99%
“…This perception includes both good and bad aspects. Xie et al (2022) studied the relationship between innovation characteristics and purchase intention. They found that consumers interested in emerging technologies are more likely to accept new energy vehicles because new technologies attract them to buy.…”
Section: Literature Review and Conceptual Framework Consumer Purchase...mentioning
confidence: 99%